Materials Characterization - Pérez Campos, Ramiro.; Pérez Campos, Ramiro.; Contreras Cuevas, Antonio.; Contreras Cuevas, Antonio.; Esparza Muñoz, Rodrigo.; Esparza Muñoz, Rodrigo. (Springer International Publishing : Imprint: Springer, 2015)
This book covers novel research results for process and techniques of materials characterization for a wide range of materials. The authors provide a comprehensive overview of the aspects of structural and chemical characterization of these materials.  The articles contained in this book covers state of the art and experimental techniques commonly used in modern materials characterization. The book includes theoretical models and numerous illustrations of structural and chemical characterization properties.